Calculus 1 - implicit differentiation
posted by Cupcake .
I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4.
I would appreciate any help that can be offered.
Just differtiate each term with respect to x, remembering that y is a function of x. You often end up with an expression for y' that involves both x and y, but is is a valid equation. You may have to evaluate y before you can calculate y'. Here is what you get:
x*dy/dx + y + 2 + 6x = 0
dy/dx = -(y + 2 + 6x)/x
= -(y+2)/x -6